Made in Mexico : Energy Reform and Manufacturing Growth - Alvarez, Jorge (IMF Working Papers; Working Paper, 2015)
This paper assesses the real effects of the energy reform in Mexico by looking at its impact on manufacturing output through changes in energy prices. Using sub-sector and state-level manufacturing output data, along with past variation in energy prices, we find electricity prices--relative to oil and gas--to be more important in the manufacturing process, with a one standard deviation reduction in electricity prices leading to a 2.8 percent increase in manufacturing output. Our estimated elasticities together with plausible reductions in electricity tariffs derived from the energy reform, could increase manufacturing output by up to 3.6 percent, and overall real GDP by 0.6 percent. Larger reductions are possible over the long run if increased efficiency in the sector leads electricity prices to converge to U.S. levels. Moreover, including the impact of lower electricity tariffs on the services sector, could lead to significantly larger effects on GDP. Accounting for endogeneity of unit labor costs in a panel VAR setting leads to an additional indirect channel which amplifies the impact of electricity prices on output.